Penerapan Model Pembelajaran Kooperatif Tipe Think Pair Share Dengan Menggunakan Media Visual untuk Meningkatkan Hasil Belajar Materi Persamaan Dasar Akuntansi (Pendidikan Ekonomi, 2013)
The purpose of this research is to know  the  the teacher’s activity, student’s activity, student learning’s outcomes, student’s respons, excellences and constraints after applying learning by visual media and cooperative learning model by Think Pair Share type in  basic accounting equation in SMA Negeri 22 Surabaya. This type of research is used classroom action research (CAR), Learning process of this research was done in three cycle. Every cycle has four research step that is : planning, acting and observing, reflecting and revising. He results of revision in the form of evaluation is a reference for the implementation of the next round. The  research  results  show  that  application  of  cooperative  learning  model  TPS  type  with  visual media which apply to student of XI IPS 2 SMA negeri 22 Surabaya effectively enough. Teacher’s activity result show that there have been increase.  It was showed from student activity while learning activity having change from activeless to be active and more focus to matery.  Exhaustiveness of student learning’s outcomes can be seen from the test results, in the first cycle the student’s average value 66, 88 in cycle II 77, 0 and the third cycle the average value of 86.89. Responses of students in the use of visual media more attractive for students. And excellence of this learning is students more active in participating of learning activities. Key Words: cooperative learning, visual media, improved learning outcomes